2019
DOI: 10.1111/clr.13491
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective case series evaluating the outcome of implants with low primary stability

Abstract: Objectives There is a need of more studies on whether low primary implant stability would negatively influence the success of implant therapy. Therefore, this retrospective study analyses outcomes of implants placed with low primary stability and factors that may be related to implant failures. Material and methods This retrospective study included 156 patients, restored with 169 implants that presented manual rotation within an observed follow‐up time of a minimum of 34 days and a maximum of 9.28 years. Descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Though several previous preclinical and clinical studies have found successful osseointegration even in loosely placed implants that completely lack initial mechanical stability, 3,15,17 clinicians still focus Two SI group implants which showed insertion torque lower than 30 Ncm were regarded as immediate loading failure and excluded. These implants were submerged for 3 months, and delayed loading protocol was applied.…”
Section: Insertion Torque and Isqmentioning
confidence: 99%
See 1 more Smart Citation
“…Though several previous preclinical and clinical studies have found successful osseointegration even in loosely placed implants that completely lack initial mechanical stability, 3,15,17 clinicians still focus Two SI group implants which showed insertion torque lower than 30 Ncm were regarded as immediate loading failure and excluded. These implants were submerged for 3 months, and delayed loading protocol was applied.…”
Section: Insertion Torque and Isqmentioning
confidence: 99%
“…3,15,16 Furthermore, a recent retrospective clinical study found the long-term success of loosely placed implants when they were left undisturbed for several months before loading. 17 However, since it is not possible to leave implants undisturbed in the immediate-loading protocol, it is still important to achieve sufficient initial stability. Successful outcomes of immediate loading have mainly been reported in cases of full-mouth rehabilitation with overdentures, since the cross-arch stabilization achieved by splinting was thought to minimize micromotion of the implants.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of the techniques and materials adopted has allowed more doctors and patients to use this type of therapy, making possible the placement of implant elements in very hard situations where only a few years ago the professional would have chosen a different therapeutic choice [ 36 ]. One of the main principles for successful therapy is the achievement of suitable primary stability during the implant placement [ 37 ] in respect to the biology of the host [ 38 ] and factors depending on the invasiveness of the operation; the more the preparation of the implant site will be performed in an atraumatic way by avoiding the overheating, and so the necrosis of the site, the more we will be able to respect tissues of the host by avoiding intra- and post-operation complications (bleeding, swelling, local infection, invasion of the noble structures adjacent to the surgery, implant early loss, inadequate healing of hard and soft tissues involved during the operation, presence and/or formation of pus immediately after the operation, pain, alteration of the sensitivity of the area) [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the surgery, we may assess the primary stability of the placed implants, a value that indicates the contact of the implant surface with the surrounding bone [ 42 ]; after this, the secondary stability will follow, which is reached after the processes of remodeling and healing of the bone [ 43 ]; usually, the achievement of good primary stability will be followed by correct secondary stability [ 44 ]. In this way, the dynamic functional response of the bone tissue is determined by the bone-to-implant contact percentage (BIC), which is constantly interested in remodeling processes under the functional loading [ 25 , 26 , 40 , 41 , 42 , 43 , 45 , 46 , 47 , 48 ]. In order to assess the implant stability, we may use an index called the implant stability quotient (ISQ), a unit of measurement, which allows us to assess the degree of integration of the placed implants [ 49 ]; the clinical range of the ISQ is ranged between 55 and 80, and if the value is higher than 65, it is commonly accepted as a favorable situation for implant stability; on the contrary, values under 45 are considered as insufficient implant stability [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, delayed loading might be safer given that a mature bone structure lining the fixture surface was observed histologically and high ISQ and IST values were observed at 4 and 8 weeks, which is consistent with the findings of previous preclinical experiments (Jung et al, 2012, 2014). The safety of delayed loading was also verified by a recent retrospective clinical study, which found favourable osseointegration and survival rates for implants with a SLA surface that exhibited rotational movements when they were first placed (Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 84%